2021
DOI: 10.1021/acs.inorgchem.0c03563
|View full text |Cite
|
Sign up to set email alerts
|

Diphosphinoboranes as Intramolecular Frustrated Lewis Pairs: P–B–P Bond Systems for the Activation of Dihydrogen, Carbon Dioxide, and Phenyl Isocyanate

Abstract: Herein, we present the first example of the activation of small molecules by P–B–P bond systems. The reactivity study involves reactions of two selected diphosphinoboranes, ( t -Bu 2 P) 2 BPh ( 1′ ) and (Cy 2 P) 2 BN i Pr 2 ( 2 ), that differ in terms of their structural and electronic properties for the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…26 Despite the presence of one to three B-P bonds, these systems retain Lewis acidic and Lewis basic character of the reactive boron and phosphorus centres and behave as intramolecular FLPs to activate H 2 , CO 2 , other heterocumulenes, SO 2 , N 2 O, and BH 3 . 24,[26][27][28] As a continuation of our previous studies, we decided to introduce this research concept to cationic boron compounds and synthesize low-coordinate boronic cations possessing B-P functionality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…26 Despite the presence of one to three B-P bonds, these systems retain Lewis acidic and Lewis basic character of the reactive boron and phosphorus centres and behave as intramolecular FLPs to activate H 2 , CO 2 , other heterocumulenes, SO 2 , N 2 O, and BH 3 . 24,[26][27][28] As a continuation of our previous studies, we decided to introduce this research concept to cationic boron compounds and synthesize low-coordinate boronic cations possessing B-P functionality.…”
mentioning
confidence: 99%
“…Interestingly, in the case of ambiphilic species containing tri-coordinate B atoms, such as phosphinoboranes and diphosphinoboranes, the small molecules are inserted into the B-P bond (except H 2 ). 24,27,28,36 Similar to the product of the reaction of the phosphinoborinium cation with benzophenone, the B-P bond is retained in adducts of neutral phosphaborene (containing dicoordinate B atom) with ketones, which were further utilized in phospha-bora-Wittig reaction. 37 In conclusion, we have provided a simple method for the generation of phosphinoborinium cation intermediates utilizing synthetically accessible bromophosphinoboranes.…”
mentioning
confidence: 99%
“…The chemistry of diphosphinoboranes has been explored to a lesser extent than that of other P–B systems (Chart B). Most synthesis attempts have been made by Nöth et al Recently, we vastly expanded the chemistry of these compounds, not only by the synthesis and isolation of several new diphosphinoboranes but also by revealing their potential in the activation of small molecules . Our preliminary research on the reactivity of selected diphosphinoboranes revealed that these species react with isocyanates, CO 2 , and H 2 .…”
Section: Introductionmentioning
confidence: 90%
“…Our preliminary research on the reactivity of selected diphosphinoboranes revealed that these species react with isocyanates, CO 2 , and H 2 . We have also reported the very first P–B system that activates both H 2 and CO 2 …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation